Spectroscopic and Microscopic Approaches for Investigating the Dynamic Interactions of Anti-microbial Peptides With Membranes and Cells - Clayton, Andrew H. A. (Frontiers in Medical Technology, 2021)
The emergence of microbes resistant to conventional antibiotics is a burgeoning threat to humanity with significant impacts on the health of people and on the health system itself. Antimicrobial peptides hold promise as potential future alternatives to conventional drugs because they form an integral part of the defense systems of other species in the animal, plant and fungal kingdoms. To aid the design of the next generation of antimicrobial peptides optimized for human use, we must first understand the mechanism of action of existing antimicrobial peptides with their targets, ideally in the context of the complex landscape of the living (microbial) cell. Advances in lasers, optics, detectors, fluid dynamics and various probes has enabled the experimenter to measure the kinetics of molecule-membrane, molecule-molecule and molecule-cell interactions with increasing spatial and temporal resolution. The purpose of this review is to highlight studies into these dynamic interactions with a view to improving our understanding of antimicrobial peptide mechanisms.